2017
DOI: 10.1186/s12883-017-0909-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment of spinal cord injury in rat model

Abstract: BackgroundThe purpose of this study was to investigate the therapeutic effects and mechanisms of hyperbaric oxygen (HBO) treatment on rats following spinal cord injury (SCI).MethodsA total of 45 Sprague-Dawley (SD) rats were randomly divided into three groups. Sham-SCI group was surgically exposed but not subjected to the SCI procedure. SCI-control group was administered SCI and treated with regular air. SCI-HBO group was administered SCI and HBO treatment. Neuromotor functions were examined using the Basso, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…The number of HBO sessions used in clinical medicine has not been firmly standardized as it substantially depends on the given medical condition; it could range from several to 60 sessions (Mathieu et al 2017). In animal experiments, the number of HBO exposures usually ranges between 1 and 15 (Ay et al 2007, Ding et al 2017, Limirio et al 2018, Sun et al 2017; studies on HBO impact on ex vivo models using various cell types usually report from 1 to 7 HBO exposures (Kang et al 2004) and document that the effect of treatment is detectable even after a single exposure. For our experiments we have thus selected conditions mimicking chronic HBO treatment on the cellular model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of HBO sessions used in clinical medicine has not been firmly standardized as it substantially depends on the given medical condition; it could range from several to 60 sessions (Mathieu et al 2017). In animal experiments, the number of HBO exposures usually ranges between 1 and 15 (Ay et al 2007, Ding et al 2017, Limirio et al 2018, Sun et al 2017; studies on HBO impact on ex vivo models using various cell types usually report from 1 to 7 HBO exposures (Kang et al 2004) and document that the effect of treatment is detectable even after a single exposure. For our experiments we have thus selected conditions mimicking chronic HBO treatment on the cellular model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that ROS production increases in HBO conditions, although oxidative susceptibility varies with the cell type, parameters of HBO therapy and number of exposures (Jang et al 2018, Simsek et al 2011. Literature data on SOD activity in HBO-treated subjects frequently document its increase going either in parallel with elevated ROS production and markers of oxidative stress (Simsek et al 2011) or fully compensating for oxidative damage (Sun et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 44 Results of another study which was investigated the mechanisms of HBOT following SCI, suggested that reducing lipid oxidation and oxygen free radicals is one of the mechanisms. 45 Sun et al 46 documented that HBO significantly improved the recovery of neuronal function and fractional anisotropy compared to SCI group on days 7, 14, and 21 after SCI. Recently, it was documented that HBOT improves neurological disorders by amelioration of apoptosis and suppressing dendritic/synaptic degeneration through upregulating the brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase B signaling pathways in the anterior horn of spinal cord after SCI.…”
Section: N V Ivo S Tudiesmentioning
confidence: 99%
“…Utilizing a rodent model of TBI, HBOT initiated at 3 h after cortical deformation induction attenuated symptoms after histopathological analysis [ 59 ]. Another murine model of TBI offered evidence that HBOT-induced cognitive and learning regenerative abilities were preserved from 3 h after injury to 7 days [ 13 ]. While experimental protocols, such as therapeutic windows, may vary, HBOT consistently provides neuroprotection for acute TBI [ 60 ].…”
Section: Implications Of Hbot In Other Neurological and Non-neurolmentioning
confidence: 99%
“…This suggests that similar mechanisms of HBOT can be demonstrated with lower tensions of oxygen. Additionally, HBOT has also proven beneficial in the treatment of other pathological diseases, including traumatic brain injury (TBI), spinal cord injury (SCI), and stroke [ 13 ]. Currently, there are few treatment options available for many neurological diseases; however, experimental studies utilizing HBOT demonstrate promising results.…”
Section: Introductionmentioning
confidence: 99%